Dakwah Ala Anwar Zahid: Menjinakkan Islam Normatif Menjadi Islam Lokal Yang Mengglobal: Pandangan Kritis Terhadap Pola Dakwah yang Disampaikan Anwar Zahid di Beberapa Video Youtube-nya - Intihaul Khiyaroh (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
The phenomenon of the preaching of Anwar Zahid is very different from da'wah in general, using a different concept that is as if Anwar Zahid is now a rising artist. This preacher began to be famous since 2011 and was in demand by many people, ranging from adolescents to adulthood. Pendakwah which carries the theme of locality where normative Islam is tamed into Islam that is easily understood by everyone. So far, Muslims understand the Qur'an and Hadith contextually; with this Anwar Zahid Islam can be accepted by all groups. As if the power relations of Anwar Zahid had tamed Muslims who began far away from his book. Local relations with the global and feriperi (center and edge) were created by Anwar Zahid because seeing the community, especially the East Java region, was no longer role model in the life of the variety. mosques in public sermons are only considered as a formality in the routine agenda without taking knowledge or new things in the material presented. Anwar Zahid seemed to hit the local by materializing. When tamed it is not solely submissive but negotiates.